Design of STEM-based E-Student Worksheet Global Warming to Improve High School Students' Critical Thinking Skills - Sahri Ropiah Lubis; Riyasni, Selma; Yurnetti, Yurnetti; Novitra, Fuja (Journal of Innovative Physics Teaching, 2025)
This research was motivated by the importance of critical thinking skills in understanding environmental issues such as global warming. Preliminary findings showed that the critical thinking skills of Grade X students at SMAN 3 Padang were still low, reaching only 29.67%. Learning also remained limited to the use of student worksheets that were not STEM-based and lacked optimal technology integration. This study aimed to develop a STEM-integrated E-student worksheet to support interactive learning and improve students’ critical thinking skills. The study used a Research and Development (R&D) method with the 4-D model (Define, Design, Develop, Disseminate), limited to the Develop stage. The product was created using Liveworksheets and validated by experts, physics teachers, and students. The expert validation achieved an average score of 0.94 (valid), covering material substance (0.95), instructional design (0.96), visual communication (0.98), software use (0.87), STEM assessment (0.91), and critical thinking assessment (0.95). Practicality tests resulted in 95% from teachers and 92% from students, categorized as very practical. Thus, the STEM-based E-student worksheet is valid, practical, and potentially improves students’ critical thinking skills.